Mali : 2010 Article IV Consultation, Fourth Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2010)
Despite the global financial and economic crisis, implementation of the government's economic and financial program was broadly satisfactory. Growth was sustained, and the balance of payments improved markedly. The implementation of structural reforms with regard to state enterprises and the strengthening of public finances are progressing satisfactorily. Mali's exchange regime and real exchange rate remain broadly appropriate, and it is at low risk of debt distress. Mali is highly vulnerable to external shocks. The provision of data is broadly adequate for IMF surveillance.